The Impact of Aging, Psychotic Symptoms, Medication, and Brain-Derived Neurotrophic Factor on Cognitive Impairment in Japanese Chronic Schizophrenia Patients - Atake, Kiyokazu; Nakamura, Tomoyuki; Ueda, Nobuhisa; Hori, Hikaru; Katsuki, Asuka; Yoshimura, Reiji (Frontiers in Psychiatry, 2018)
Background Cognitive impairment in schizophrenia can result in considerable difficulty in performing functions of daily life or social rehabilitation. Cognitive impairment in schizophrenia is related to various factors, such as the psychotic severity, aging, medication and brain-derived neurotrophic factor (BDNF). To date, however, no studies investigating the impact of these factors on cognitive functioning in chronic schizophrenia patients have been performed. Objective The aim of this study is to identify those factors that influence the cognitive functioning in patients with chronic schizophrenia. Methods Sixty-five of 116 long-term hospitalized chronic schizophrenia patients (63.8±12.1 years old, M/F=29/36) were enrolled this cross-sectional study. We investigated the relationship among the patients’ age, psychotic severity, treatment medication, serum BDNF levels and cognitive functioning (measured by the Japanese-language version of the Brief Assessment of Cognition in Schizophrenia; BACS-J). Additionally, we performed a multivariable linear regression analysis. Results According to the partial correlation analysis, certain parameters (i.e., age, chlorpromazine (CP) equivalent, biperiden (BP) equivalent, and serum BDNF) were significantly correlated with cognitive functioning, including working memory (WM), motor function (MF), attention and processing speed (AP) and executive function (EF). For the multivariate analysis, the MF component, which had the highest correlation, was selected as the dependent variable, and the independent variables included age, ManS total score, CP equivalent, BP equivalent, serum BDNF, estimated full scale IQ, and years of education. According to the multiple regression analysis of this model, R (multiple regression coefficient) was 0.542, the adjusted R2 (coefficient of determination) was 0.201 and only BP equivalent (β=-0.305, p=0.030), but not age, ManS score, CP equivalent or serum BDNF, could significantly explain MF at the 5% significant level. Conclusion: In conclusion, aging, medication (administering more antipsychotics or anticholinergics) and serum BDNF concentration are significantly correlated with cognitive dysfunction in chronic schizophrenia patients but not with the severity of psychotic symptoms. Furthermore, only the anticholinergic dosage had a significant causal relationship with MF. Thus, the use of anticholinergics in chronic schizophrenia patients with deteriorating cognitive functioning must be reconsidered.